PELUANG DAN TANTANGAN MERGER BANK SYARIAH MILIK NEGARA DI INDONESIA PADA MASA PANDEMI COVID-19 - Fiqri, Alfany Arga Alil; Azzahra, Minerva Maharani; Branitasandini, Khansa Dzakiyah; Pimada, Laila Masruro (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2021)
The existence of COVID-19 in Indonesia had an impact on economy, including banking sector. However, sharia banking sector didn’t show a positive trend. However, even though sharia banking shows a positive trend, penetration rate of Islamic banking market in Indonesia is still relatively small when compared to conventional banking. That has made government decide to make a merger policy in state-owned sharia banking in hope that it can increase market penetration in Indonesia. This article is written to analyze about opportunities and challenges of merger policy for sharia banking considering the large role of sharia banking in improving country's economy. On the other hand, this policy was implemented in the midst of the COVID-19 pandemic. This article uses qualitative data analysis with descriptive methods and through a literature study approach. The data analysis focuses on the opportunities and challenges of the sharia banking merger policy by Indonesian’s government. Researchers use secondary data as a source for making articles. Based on research results, the formation of Bank Syariah Indonesia (BSI) as a result of merger provides many opportunities such as increasing assets, expanding market penetration, and operating cost efficiency. Meanwhile, financing and operational risk are two big challenges that need attention. This study contributes as inputs for stakeholders’ decisions in developing Islamic bank and finance